THE SIGNIFICANCE OF LEGAL REGULATION IN ENSURING CYBER SECURITY IN THE CONDITIONS OF WAR: EXPERIENCE FOR UKRAINE - Horulko, Vladyslav (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2024)
Introduction. In the vast majority of countries, there is a constant trend towards a significant increase in the number and expansion of the spectrum of cyber-attacks with the aim of violating the confidentiality, integrity and availability of state information resources, in particular those distributed on the Internet and objects of critical information infrastructure. Summary of main results. The large-scale deployment of a hybrid war against our state seriously affects all aspects of social life. To a large extent, the strategic success of countering the challenges of hybrid warfare depends on the effective and quality of the legal response. Ensuring an adequate level of cyber security is difficult to imagine without clearly planned joint actions and measures developed by responsible entities, which must be synchronized and implemented according to a single strategic plan and development vector of the national cyber security system of a declarative nature. That is why cyber security in most countries of the world is recognized as an important component of national security, the provision of which is impossible without the formation and functioning of a national system in the field of cyber security, which is based on such principles as respect for the principles and norms of international law, protection of fundamental values defined by current legislation, protection national interests in cyberspace. It is emphasized that the state’s national security largely depends on the state of cyber security. It has been proven that hybrid war significantly increases the impact of cyber threats on Ukrainian society and actualizes the danger of targeted cyber attacks as a tool of aggression against our state in the context of global trends regarding threats in cyberspace. Conclusions. In the process of conducting the research, we formulated conclusions in which special attention was paid to the peculiarities of the current state of functioning of the legislation on cyber security and considered promising directions for its improvement in the future, which, in turn, will become the basis for improving the administrative and legal regulation of cyber security in Ukraine.